Pyrolysis of bamboo over Ce/Fe composite metal oxide catalyst to enhance the production of hydrocarbons and ketonic hydrocarbon precursors. (24th January 2021) - Du, Haoran; Zhong, Zhaoping; Zhang, Bo; Fu, Jimin; Li, Zhaoying
Abstract: To obtain high‐value bio‐oil, pure ceria (CeO2 ) and a series of Ce/Fe composite metal oxides were synthesized via precipitation method and were used to enhance hydrocarbons and ketones production during catalytic pyrolysis of bamboo sawdust. The characterization results were comprehensively analyzed and revealed that doping CeO2 with Fe promoted the formation of a solid solution structure, which further increased the surface area and number of oxygen vacancies of the catalyst for deoxygenation. Experimental consequences demonstrated that, compared to non‐catalytic trial, the catalytic pyrolysis over CeO2 generated lower amounts of acids and aldehydes, and enhanced the conversion of large oxygenates to monofunctional hydrocarbon precursors via decarboxylation, deoxidation, and ketonization. The concentrations of hydrocarbons and ketones obtained over Ce/Fe catalysts were significantly higher than those obtained over CeO2, and that was attributed to the higher surface area and oxygen storage capacity of Ce/Fe catalysts. Particularly, the composite catalyst with the Ce/Fe molar ratio of 4 (Ce0.8 Fe0.2 ) presented the most optimal deoxidation capacity in this study. The relative concentration of hydrocarbons generated over Ce0.8 Fe0.2 was the highest, and monocyclic aromatics and short‐chain aliphatic hydrocarbons accounted for 47.13% and 29.72%, respectively, of the total hydrocarbons. Simultaneously, the amount of ketones, the main hydrocarbon precursors, obtained over Ce0.8 Fe0.2 was significantly higher than that obtained over CeO2, and the fraction of linear and cyclic ketones of the total ketones increased from 45.96% for the non‐catalytic pyrolysis to 97.57%. This further confirmed that the mesoporous Ce/Fe composite catalysts efficiently catalyzed the aldol condensation and ketonization reactions. Abstract : Deoxygenation mechanism performed by synthesized Ce/Fe composite metal oxide catalyst.